2017
DOI: 10.1021/acsbiomaterials.6b00706
|View full text |Cite
|
Sign up to set email alerts
|

Dual Affinity Heparin-Based Hydrogels Achieve Pro-Regenerative Immunomodulation and Microvascular Remodeling

Abstract: The immune response to biomaterial implants critically regulates functional outcomes such as vascularization, transplant integration/survival, and fibrosis. To create “immunologically smart” materials, the host-material response may be engineered to optimize the recruitment of pro-regenerative leukocyte subsets which mature into corresponding wound-healing macrophages. We have recently identified a unique feature of pro-regenerative Ly6Clow monocytes that is a higher expression of both the bioactive lipid rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…Inability of local delivery of FTY720 to induce pro-regenerative monocyte and macrophage recruitment and protein production after murine RCT contrasts with prior studies indicating such effects in the murine dorsal skin window model [9,10,21]. The disparity may suggest that the effects of FTY720 on inflammation are highly context-dependent.…”
Section: Discussionmentioning
confidence: 73%
“…Inability of local delivery of FTY720 to induce pro-regenerative monocyte and macrophage recruitment and protein production after murine RCT contrasts with prior studies indicating such effects in the murine dorsal skin window model [9,10,21]. The disparity may suggest that the effects of FTY720 on inflammation are highly context-dependent.…”
Section: Discussionmentioning
confidence: 73%
“…Of note, this problem was not observed for systemic FTY-720 delivery 160,162 , indicating that the route of delivery impacts its islet toxicity. Coupling FTY-720 with chemotactic stromal derived 162 factor-1α (SDF-1α/CXCL12) can mitigate these negative impacts by the recruitment of woundresolving macrophages 163 , but this has not yet been tested in islet transplants. 160,161 Material-based intranodal drug delivery or sphingosine-1-phosphate analogues with better receptor selectivity, such as KRP203 164 , could be investigated to overcome this challenge.…”
Section: Suppression Of Allo-and Autograft Rejection-mentioning
confidence: 99%
“…Recently, it has reported that a bifunctional hydrogel loaded with the sphingosine analogs, FTY720 and SDF-1α, enhances the recruitment of anti-inflammatory monocytes and promotes microvascular remodeling, thus promoting of tissue repair. This dualaffinity hydrogel overcomes the challenge of codelivering two physiochemically distinct molecules, and the corelease of FTY720 and SDF-1α yields superior proregenerative biological effects over either factor alone [117].…”
Section: Perspectivesmentioning
confidence: 99%